'Do not break the cold chain!' The introduction of a system for deep frozen food in Sweden 1940–1960*. Issue 1 (2nd January 2017) - Sandgren, Fredrik
ABSTRACT: The introduction of deep frozen food in Sweden took place from 1945. The development was rapid and by 1960 Sweden had become the worlds' second largest per capita consumer of frozen foods. Grocers were a key group that needed to be convinced of the gains of deep freezing. Journals from retail businesses and peak retail trade associations are studied to discover how knowledge about deep freezing was conveyed to grocers. Articles and advertisements show what arguments could be found for and against deep freezing and which informants that were active. Grocers were presented with a balanced account of the pros and cons of deep freezing already by the late 1940s. When the experience of frozen foods and handling of freezing equipment increased in the 1950s, these experiences were conveyed to the grocers, creating a broad but not entirely uncritical knowledge base for further diffusion. Most advertisements concerned equipment for deep freezing, rather than deep frozen foods. The general view in all studied journals was positive towards deep freezing. The diffusion of knowledge made through the studied journals suggests they played an important role for the establishment of the system of frozen food in Sweden.